Pengaruh Celebrity Endorse dan Product Signatureness Terhadap Purchase Intention Product Sunaka Jewelry - Erawati, Ni Wayan Sara; Wimba, I Gusti Ayu; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of the study was to determine the effect of Celebrity Endorse and Ptoduct Signatureness partially and simultaneously on the Purchase Intention of Sunaka Jewelry products. Data collection methods used were observation, interviews, and questionnaires. The population in this study were active followers of Sunaka Jewelry’s instagram, the sample was determined by the slovin formula totaling 99 respondents. The data analysis technique used instrument test, classical assumption test and multiple linear regression test. The results of this study are that there is a positive and significant influence between Celebrity Endorsement on Purchase Intention of Sunaka Jewelry Products. There is a positive and significant influence between Product Signatureness on the Purchase Intention of Sunaka Jewelry’s Product. Simultaneously there is a positive and significant effect between Celebrity Endorse and Product Signatureness on Sunaka Jewelry’s Purchase Intention Product. Suggestions that can be conveyed by researchers are that Sunaka Jewelry is expected to pay more attention to consumer tastes when determining the characters to be used for their product endorsers and to provide easier access for consumers about the products to be offered